2016
DOI: 10.12776/ams.v22i1.690
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Microstructure of Cold-Rolled if Steel

Abstract: With the emerge of vacuum technology, it is possible to produce ultra low carbon (ULC) steels with carbon content of less than 0.005 %mass which is called interstitial free (IF) steels. In this study, strength and microstructure of IF steel after cold-rolling have been determined. The initial steel plates were cold-rolled using two different cold reductions (CR) as 80 and 90% in total, thereafter the steel sheets were cut into specimens for tensile test and optical microscopy. Ultimate tensile strength (UTS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Thus, it is necessary to optimize the processing conditions to increase the ductility because the microstructure with high dislocation density increases the strength significantly. The YS of the initial steel was 137 MPa, indicates that the strength of the present study was lower than that of the automotive IF steels, which exhibit typically 200-280 MPa of YS and 30-47% of EL [15][16][17]. The YS after baking is usually used to evaluate the dent resistance of the steel; therefore, BH response is essential for the products which are made of the low strength IF steel when the paint is baked.…”
Section: Mechanical Properties and Microstructure Of The Initial If Smentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, it is necessary to optimize the processing conditions to increase the ductility because the microstructure with high dislocation density increases the strength significantly. The YS of the initial steel was 137 MPa, indicates that the strength of the present study was lower than that of the automotive IF steels, which exhibit typically 200-280 MPa of YS and 30-47% of EL [15][16][17]. The YS after baking is usually used to evaluate the dent resistance of the steel; therefore, BH response is essential for the products which are made of the low strength IF steel when the paint is baked.…”
Section: Mechanical Properties and Microstructure Of The Initial If Smentioning
confidence: 76%
“…This conclusion consolidated the explanation of that the residual stress increased the strengths of the baked steels as listed in table 3. Concerning the dependence of yield stress on microstructural parameters, the Hall-Petch relationship is usually used [10,15,21]:…”
Section: Fig 4 Effect Of Pre-strain (A) and Baking Temperature (B) mentioning
confidence: 99%
“…Since the mechanical properties of the steel have been known to depend on the compositions, deformation, and heat treatment, the alloying elements, such as Si and Mn, which were added to compensate for the softening effect of ULC content, contribute to the strengthening by solid solution hardening. Mn has an important role in steel due to improving steel in terms of its hot workability, steel without Mn has a trend to be brittle at high temperatures [6,9,10]. The used raw materials consisted of graphite powder and high-purity metals such as electrolyzed iron (Fe), manganese (Mn), and copper (Cu) with the calculated ratios.…”
Section: Methodsmentioning
confidence: 99%
“…In combination with Cu additions, low carbon content is essential for attaining the desired effects, and many research works have been carried out to clarify the benefits of the alloyed Cu via hot rolling or heat treatment to make further gains in the quality of the Cu-containing steel. The demands for steel with excellent formability from the automotive industry have accelerated the progress in the steelmaking process, leading to the development of ultra-low carbon (ULC) steel containing carbon less than 0.01 wt.% [9,10]. On the other hand, it has been found that the solute Cu can improve the mechanical properties of ferritic steel such as ULC steel.…”
Section: Introductionmentioning
confidence: 99%
“…One of the manufacturing processes used for this type of auto parts is stamping. Currently ULC steel grades containing ultra-low carbon contents, such as the Interstitial Free (IF), are considered one of the material of great industrial interest for this type of applications due to their particular combination of mechanical properties: aptitude to deep drawing, acceptable values of mechanical resistance and a microstructure of ultrafine grain [1]. The mechanical properties can be improved by refining and rearranging the microstructure.…”
Section: Introductionmentioning
confidence: 99%